A CASE REPORT: MANAGEMENT OF FETAL MUMMIFICATION IN CAT - Nabilah Putroe Agung; Nabila Latifa Hafizsha; Rasyida Ulfa; Idham Khalid; Rizky Fitriana; Triono Basuki; Wywy GM Silaban (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Fetal mummification is a gestational disorder in animals. The mummified fetus remains in the mother's uterus until the normal gestation period. In cats, cases of fetal mummification are relatively low and often go undiagnosed, especially in cats living in the wild. Radiographic and ultrasonographic examinations are the primary diagnostic methods for identifying the fetus. A procedure known as an ovariohysterectomy can be used to address fetal mummification. This paper aims to explain the diagnostic process and treatment of fetal mummification on a cat. A 7-year-old queen weighing 3 kg presented with abdominal swelling. Palpation revealed a hard mass. Radiographic examination revealed an oval-shaped mass in the lower abdomen. The mass was removed by an ovariohysterectomy procedure. The surgical results revealed two mummified fetuses in the mother's uterus. Post-operatively, the antibiotic Clanexi®, anti-inflammatory Macrolone® and Bevalex® ointment were given. Postoperative wound healing was observed after 7 days, and the cat showed good recovery. Sterilization can reduce cases of mummification, especially in stray cats. This paper can be used as a reference for the management of mummification cases in cats.